BLACK APPLE: AN INSPECT OF ITS NUTRITIONAL AND MEDICINAL HEALTH BENEFITS (International Journal of Food and Nutritional Sciences, 2024)
Due to their dark meat and skin, black apples (Malus domestica) are a rare and lesser-known kind of apple. Black apples are quite uncommon, yet research has shown that they offer remarkable nutritional and therapeutic qualities. The purpose of this study is to provide an overview of the most recent research on the bioactive ingredients, antioxidant activity, and possible health advantages of black apples.Black apples have a substantially greater antioxidant and polyphenol content than regular apples, which makes them a fruit that shows promise in lowering the risk of chronic illnesses including cancer, cardiovascular disease, and neurological problems. Black apples have also long been utilized in folk medicine due to their antidiabetic, antibacterial, and anti-inflammatory qualities.This abstract emphasizes how beneficial black apples may be as a dietary supplement and medical tool, indicating the need for more study and investigation into these uses.